Tailor-made hydroponic recipes for the production of high quality medicinal and aromatic plants - Chrysargyris, Antonios; Tzortzakis, Nikos G. (My University, 2021)
There is an increasing interest of the food industry, academia, and health sciences on medicinal and aromatic plants (MAP), as a source of antioxidants, nutrients and essential oils (EO). Considering the various metabolic functions of minerals (nitrogen - N, potassium - K and phosphorus - P) and the lack of information on the mineral needs in several MAP species, each species requires its own nutrient management. To that direction, hydroponics is a tool to fully control plant development for stable and reproducible growth parameters, mineral content, antioxidants and EO constituents. The present study contributes to address such issue, defining the nutrient demand of two of the most popular medicinal plants, lavender and spearmint. Lavender was grown in perlite, in an open cycle management system, while spearmint was grown in deep flow technique (DFT), in a closed system. Different concentrations of N, K and P were applied and aerial parts from both plants were collected, to assess the EO yield and quality. Results indicated that the lavender EO may be affected by the ratio and amount of N, K, and P. Nitrogen levels greater than 200 mg L-1 resulted in lower camphor percentage (higher oil quality). High carvone content (high oil quality) was observed when N>200 mg L-1 was applied. Custom made recipes for each plant species can be recommended depending on the production needs (food, pharmaceuticals, cosmetics, plant protection). What industry is lacking is a way to standardize the cultivation of these plants, in order to elevate quality and reduce batch-to-batch variation.
Keywords: Antioxidants; Essential oil; Lavandula angustifolia; Mentha spicata; Nutrient solution; Quality; Soilless culture